2003
DOI: 10.1124/jpet.103.061770
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Inhibition of Hepatic Uptake and Efflux Significantly Changes Metabolism: Hepatic Enzyme-Transporter Interplay

Abstract: The disposition of digoxin and the influence of the organic anion transporting polypeptide (Oatp)2 inhibitor rifampicin and the P-glycoprotein (P-gp) inhibitor quinidine on its hepatic disposition were examined in the isolated perfused rat liver. Livers from groups of rats were perfused in a recirculatory manner after a bolus dose of digoxin (10 g), a dual substrate for Oatp2 and P-gp as well as CYP3A. Perfusions of digoxin were also examined in groups of rats in the presence of the inhibitors: rifampicin (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 32 publications
5
92
2
Order By: Relevance
“…In contrast to the results (for humans) reported here, which show digoxin is not a substrate of hepatic OATPs, it has been shown that digoxin is a substrate of hepatic Oatp1a4 in rats (Noé et al, 1997), although there is no ortholog of Oatp1a4 in humans. In addition, amiodarone, quinidine, and rifampicin have been shown to inhibit uptake of digoxin in rat hepatocytes (Lambert et al, 1989;Hedman and Meijer, 1998;Olinga et al, 2001;Kodawara et al, 2002;Lam and Benet, 2004;Lau et al, 2004). None of these compounds inhibited digoxin uptake in SCHH in the current study.…”
Section: Discussioncontrasting
confidence: 37%
“…In contrast to the results (for humans) reported here, which show digoxin is not a substrate of hepatic OATPs, it has been shown that digoxin is a substrate of hepatic Oatp1a4 in rats (Noé et al, 1997), although there is no ortholog of Oatp1a4 in humans. In addition, amiodarone, quinidine, and rifampicin have been shown to inhibit uptake of digoxin in rat hepatocytes (Lambert et al, 1989;Hedman and Meijer, 1998;Olinga et al, 2001;Kodawara et al, 2002;Lam and Benet, 2004;Lau et al, 2004). None of these compounds inhibited digoxin uptake in SCHH in the current study.…”
Section: Discussioncontrasting
confidence: 37%
“…S5. Those profiles were strikingly similar to corresponding referent quinidine and rifampicin profiles (Lau et al, 2004) without either having undergone METABOLISM. That similarity indicates that rifampicin and quinidine metabolism was very modest.…”
Section: Downloaded Frommentioning
confidence: 51%
“…Hunt et al (2006) and Yan et al (2008a,b) describe an in silico liver composed of similarly constructed LOBULES. Because perfusate was recycled in (Lau et al, 2004), the data did not require that level of detail, so we designed, validated, and used a simpler in silico liver. The rationale for doing so is expanded on in the supplemental material.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations